Epidemiological approach and bioethical considerations on hepatitis b virus infection in children and adolescents in the state of Acre, Brazil - Gomes de Lima, Alessandre; Lima da Costa, Ruth Silva; Ferreira Bortolini, Cristiane Sores; Roque, Carolina Pinho de Assis Pereira; Ferreira, Beatriz; Leocadio de Oliveira, Vitor Hugo; Ribeiro, Ianca; Ferreira, Fábio Reis; Lobato, Cirley Maria de Oliveira; Ribeiro, Dilza Terezinha Ambros; Nunes, Rui (Acta Bioethica, 2023)
The study investigates the epidemiological aspects of hepatitis B in children and adolescents, discussing the results found in the light of bioethical principles. This is a cross-sectional, retrospective study, based on a time series of cases, whose notification data were extracted from the Notifiable Diseases Information System (SINAN) and vaccination data from the National Immunization Program Information System - SIPNI, from 2011 to 2020. 889 cases of hepatitis B were reported in the study population. Most participants were aged between 15 and 19 years old 738 (83%), female 549 (62%), brown skin color 637 (72%) living in the urban area 490 (55%) and with incomplete elementary education 279 (31%). The probable source of infection was through sexual intercourse 450 (51%). The most common clinical form was Chronic Hepatitis 496 (56%). Most of those infected with Hepatitis B were unvaccinated individuals 298 (34%). In the light of bioethics, the results show that the practice of vaccination can contemplate bioethical principles, since the degree of autonomy depends on a type of planned intervention and the greater the relationship between benefit and burden, taking into account the principles of beneficence and not maleficence, the less decisive is this autonomy.